Estimates of Type 2 Diabetes Mellitus Burden Attributable to Particulate Matter Pollution and Its 30-Year Change Patterns: A Systematic Analysis of Data From the Global Burden of Disease Study 2019 - Wu, Ying; Fu, Rongguo; Lei, Chen; Deng, Yujiao; Lou, Weiyang; Wang, Li; Zheng, Yi; Deng, Xinyue; Yang, Si; Wang, Meng; Zhai, Zhen; Zhu, Yuyao; et al. (Frontiers in Endocrinology, 2021)
Background Epidemiological trends of type 2 diabetes mellitus attributable to fine particulate matter (PM2.5) pollution remain unclear. Here, we estimated spatiotemporal trends of type 2 diabetes mellitus burden attributable to PM2.5 pollution, including ambient particulate matter pollution (APMP) and household air pollution (HAP), from 1990–2019. Methods Data were obtained from the Global Burden of Disease Study 2019 and were analyzed by age, sex, year, and location. Joinpoint regression analysis was applied in the analysis of temporal trends in type 2 diabetes mellitus burden over the 30-year period. Results Globally, PM2.5 pollution contributed to 292.5 thousand deaths and 13 million disability-adjusted life-years (DALYs) in 2019. APMP ranked third among all risk factors, causing an increase in type 2 diabetes mellitus burden from 1990, whereas impact of HAP significantly fell during the same period. Both APMP and HAP contributed the most to deaths and DALYs of type 2 diabetes mellitus among older people. However, the age-standardized death and DALY rates of type 2 diabetes mellitus attributable to APMP were greater among males and people in the middle socio-demographic index countries, especially in Southern Sub-Saharan Africa. For HAP, type 2 diabetes mellitus burden was modestly higher in females, and was highest in Oceania, which was the only region with an increase from 1990. Conclusions PM2.5 pollution resulted in substantial and increasing type 2 diabetes mellitus burden worldwide. Hence, governments and health systems should take steps to reduce air pollution to mitigate this increasing burden.